Influences of Shopping Lifestyle and Reference Groups Towards Purchase Intention of Preloved Fashion - Isma Nurhikmah Apupianti; Ujang Sumarwan; Netti Tinaprilla (Indonesian Journal of Business and Entrepreneurship (IJBE), 2019)
This research aims to analyze the influence of reference groups on shopping lifestyle and also the influence of shopping lifestyle and reference groups towards online preloved fashion’s purchase intention. This research is based on the theory of factors that influence consumer behavior developed by Engel et al., (1994). In addition, shopping lifestyle is based on the theory developed by Seock (2003) and reference groups developed by Schiffman and Kanuk (2007) and Sumarwan (2011). The design of this research was a cross-sectional study with survey method answered by online open-close ended questionnaire and interview. This research involved 201 samples which were selected by using convenience sampling. There are two endogen latent variables in this research include shopping lifestyle (shopping enjoyment, brand consciousness, price consciousness, shopping confidence, in-home shopping tendency, quality and environmental consciousness) and reference groups. Whereas exogen latent variable is purchase intention. The data obtained were processed using Structural Equation Model (SEM) method through SmartPLS 3.0. Shopping lifestyle has a significant and positive influence towards purchase intention. The highest contribution derived from shopping confidence and the lowest contribution derived from environmental consciousness. Reference groups ha a significant and positive influence on shopping lifestyle. But, reference groups ha no influence on purchase intention because it could not give the strong effects both in using and buying process.Keywords: online preloved fashion, purchase intention, reference groups, shopping lifestyle